Essential self-adjointness of Dirichlet operators of Gibbs measures on infinite products of manifolds - Antoniouk, A. Vict.; Antoniouk, A. Val.; Kondratiev, Yu. G. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We obtain the conditions of essential self-adjointness of Dirichlet operators of Gibbs measures with essential domains consisting of smooth cylindrical functions. It is proved that certain spaces of smooth functions are invariant under the action of the semigroup of the Dirichlet operator.